In silico Analysis Revealed Potential Anti-SARS-CoV-2 Main Protease Activity by the Zonulin Inhibitor Larazotide Acetate - Di Micco, Simone; Musella, Simona; Scala, Maria C.; Sala, Marina; Campiglia, Pietro; Bifulco, Giuseppe; Fasano, Alessio (Frontiers in Chemistry, 2021)
The most severe outcome of COVID-19 infection is the development of interstitial pneumonia causing acute lung injury (ALI) and/or acute respiratory distress syndrome (ARDS), both responsible for the infected patients’ mortality. ALI and ARDS are characterized by a leakage of plasma components into the lungs, compromising their ability to expand and optimally engage in gas exchange with blood, resulting in respiratory failure. We have previously reported that zonulin, a protein dictating epithelial and endothelial permeability in several districts, including the airways, is involved in ALI pathogenesis in mouse models, and that its peptide inhibitor Larazotide acetate (also named AT1001) ameliorated ALI and subsequent mortality by decreasing mucosal permeability to fluid and extravasation of neutrophils into the lungs. Thanks to the recent crystallographic resolution of the SARS-CoV-2 main protease (Mpro), an enzyme fundamental in the viral lifecycle, bound to peptidomimetic inhibitors N3 and 13b, we were able to perform molecular modeling showing that AT1001 presents structural motifs similar to co-crystallized ligands. Specifically, docking, MM-GBSA-based predictions and molecular dynamics showed that AT1001 docks extremely well in the Mpro catalytic domain through a global turn conformational arrangement without any unfavorable steric hindrance. Finally, we have observed that AT1001 can be superimposed onto the crystallized structures of N3 and 13b, establishing a higher number of interactions and accordingly a tighter binding. In vitro studies confirmed AT1001 anti-Mpro and preliminary investigation indicted an anti-viral activity. Combined, these studies suggest that AT1001, besides its well-demonstrated effect in ameliorating mucosal permeability in ALI/ARDS, may also exert a direct anti-SARS-CoV-2 effect by blocking the Mpro. AT1001 has been used extensively in a variety of animal models of ALI demonstrating robust safety and efficacy; it is currently in phase 3 trials in celiac subjects showing strong safety and efficacy profiles. We therefore propose its use as a specific anti-SARS-CoV-2 multitargeting treatment for the current pandemic.